PERAN BRAND IMAGE DALAM MEMEDIASI KUALITAS DAYA TARIK WISATA TERHADAP NIAT BERKUNJUNG KEMBALI WISATAWAN NUSANTARA KE JATILUWIH, TABANAN, BALI - Pranata, Rama Ady; Negara, I Made Kusuma; Sudana, I Putu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 10 No 2 (2022): Jurnal IPTA (December 2022)DO - 10.24843/IPTA.2022.v10.i02.p17, 2023)
This study aims to determine the role of Brand Image in mediating the influence of the quality of the Jatiluwih tourist attraction on the intention of returning domestic tourists to the Jatiluwih tourist attraction, Tabanan Regency. The sampling technique in this study was taken by purposive sampling with  sample of 100 respondents, the respondent of this research were tourists who were visiting or had visited the tourist attraction of Jatiluwih. Meanwhile, this research is quantitative by using path analysis method as a data analysis technique. In this study using literature study techniques, interviews, observation and distributing questionnaires to obtain data. The results of the path analysis on the quality of tourist attractions have a direct influence on the intention to revisit and an indirect effect through Brand Image. The magnitude of the indirect effect coefficient can be calculated by multiplying the path coefficient from the quality of tourist attraction to Brand Image with the path coefficient from Brand Image to revisit intention of 0.474 x 0.389 = 0.184. The result of the indirect effect coefficient is smaller than the direct effect (0.184 < 0.728), so it can be said that the Brand Image variable is a mediating variable in mediating the influence of the tourist attraction quality variable on the return visit intention variable.